Dosimetric evaluation of the Acuros XB algorithm for a 4 MV photon beam in head and neck intensity‐modulated radiation therapy. (8th July 2015) - Hirata, Kimiko; Nakamura, Mitsuhiro; Yoshimura, Michio; Mukumoto, Nobutaka; Nakata, Manabu; Ito, Hitoshi; Inokuchi, Haruo; Matsuo, Yukinori; Mizowaki, Takashi; Hiraoka, Masahiro
Abstract : In this study, we assessed the differences in the dose distribution of a 4 MV photon beam among different calculation algorithms: the Acuros XB (AXB) algorithm, the analytic anisotropic algorithm (AAA), and the pencil beam convolution (PBC) algorithm (ver. 11.0.31), in phantoms and in clinical intensity‐modulated radiation therapy (IMRT) plans. Homogeneous and heterogeneous, including middle‐, low‐, and high‐density, phantoms were combined to assess the percentage depth dose and lateral dose profiles among AXB, AAA, and PBC. For the phantom containing the low‐density area, AXB was in agreement with measurement within 0.5%, while the greatest differences between the AAA and PBC calculations and measurement were 2.7% and 3.6%, respectively. AXB showed agreement with measurement within 2.5% at the high‐density area, while AAA and PBC overestimated the dose by more than 4.5% and 4.0%, respectively. Furthermore, 15 IMRT plans, calculated using AXB, for oropharyngeal, hypopharyngeal, and laryngeal carcinomas were analyzed. The dose prescription was 70 Gy to 50% of the planning target volume ( PVT 70 ). Subsequently, each plan was recalculated using AAA and PBC while maintaining the AXB‐calculated monitor units, leaf motion, and beam arrangement. Additionally, nine hypopharyngeal and laryngeal cancer patients were analyzed in terms of PTV 70 for cartilaginous structures ( PVT 70 _ cartilage ). The doses covering 50% to PTV 70 calculated by AAA and PBC were 2.1 % ± 1.0 % and 3.7 % ± 0.8 % significantly higher than those using AXB, respectively ( p < 0.01 ). The increases in doses to PTV 70 _ cartilage calculated by AAA and PBC relative to AXB were 3.9% and 5.3% on average, respectively, and were relatively greater than those in the entire PVT 70 . AXB was found to be in better agreement with measurement in phantoms in heterogeneous areas for the 4 MV photon beam. Considering AXB as the standard, AAA and PBC overestimated the IMRT dose for head and neck cancer. The dosimetric differences should not be ignored, particularly with cartilaginous structures in PTV. PACS number: 87.55.‐x, 87.55.dk, 87.55.kd